Aligned Nano‐Porous Microwave Exfoliated Graphite Oxide Ionic Actuators with High Strain and Elastic Energy Density. (21st August 2013) - Ghaffari, M.; Kinsman, W.; Zhou, Y.; Murali, S.; Burlingame, Q.; Lin, M.; Ruoff, R. S.; Zhang, Q. M.
<x xml:space="preserve">Abstract</x> A high‐density aligned nanoporous activated microwave exfoliated graphite oxide (aMEGO) ionic actuator is studied. Before applying an external electric field, the cations and anions are randomly distributed in the composite. After applying the electric field, ions ingress in between the aligned aMEGO sheets through the nanopores to compensate the charges on the electrodes, resulting in the separation of neighboring sheets and unidirectional electro actuation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>